2005
DOI: 10.1051/0004-6361:20041875
|View full text |Cite
|
Sign up to set email alerts
|

Multispacecraft observations of the hard X-ray emission from the giant solar flare on 2003 November 4

Abstract: Abstract. The hard X-ray emission from the "giant" solar flare on 4 November 2003 (∼1947 UT) was observed by the hard X-ray/gamma ray spectrometer on the Ulysses spacecraft located at ∼114 degrees west of the Sun-Earth line at a distance of 5.28 AU from the Sun. A "small" hard X-ray burst during the early rise of the giant flare and a part of the decay of the hard X-ray emission associated with the giant flare were also observed by the hard X-ray imager on the RHESSI satellite located near the Earth. The maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 22 publications
0
29
0
Order By: Relevance
“…Column 5 gives the non-normalized maximum GRB count rate after correction for dead time and rollover, and columns 6 and 7 give the inferred GOES X-class intensity and its uncertainty, derived from the scaling law in Section 4.2. The Ulysses observing time range overlapped with that of RHESSI, which gives us an opportunity for direct photometric comparisons of specific events (e.g., Kane, McTiernan, and Hurley, 2005). We have done a comparison for one well-observed flare, the GOES X8.3 of 2 November 2003.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Column 5 gives the non-normalized maximum GRB count rate after correction for dead time and rollover, and columns 6 and 7 give the inferred GOES X-class intensity and its uncertainty, derived from the scaling law in Section 4.2. The Ulysses observing time range overlapped with that of RHESSI, which gives us an opportunity for direct photometric comparisons of specific events (e.g., Kane, McTiernan, and Hurley, 2005). We have done a comparison for one well-observed flare, the GOES X8.3 of 2 November 2003.…”
Section: Discussionmentioning
confidence: 99%
“…During the last (Cycle 22) and the present (23) solar cycles, Ulysses GRB successfully recorded the most energetic solar flares (Kane et al, 1995), among which the major flare of 4 November 2003, was the most notable (Kane, McTiernan, and Hurley, 2005). Kane, McTiernan, and Hurley (2005) and others have used the term "giant flare" to describe these top few flares, typically at GOES level X10 or above; they speculated that such flares utilize the bulk of the magnetically stored energy.…”
Section: The Most Energetic Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…After a dramatic increase at ∼11:02:30 UT, enormous peak flux densities of 25,000 and 11,000 sfu were reached (Kaufmann et al 2004). It was associated with an X ≥28 flare (Kane et al 2005), which may have been the largest X-ray event since…”
Section: Observationsmentioning
confidence: 99%
“…Since the strength of RHESSI lies in (1) the first imaging at high energies, (2) the high spectral resolution that allows one to resolve most of the gamma-ray lines, and (3) the high-resolution spectroscopy also at lower hard X-ray energies, we summarize some new RHESSI results in the same order: (1) imaging with RHESSI revealed the evolution of progressing reconnection along a flare loop arcade (Grigis & Benz 2005a;Li et al 2005a), the so far unexplained loop-top altitude decrease in the initial phase of flares (Veronig et al 2005a), and the obscured view of a giant flare with an energy of ≈10 34 ergs (Kane et al 2005); (2) gamma-ray line modeling with RHESSI showed us a 511 keV e ϩ /e Ϫ annihilation line that is so broad that the ambient ionized medium needs a temperature of 10 5 K, instead of the expected much lower chromospheric value (Share et al 2004);and (3) high-resolution spectroscopy with RHESSI gave us new insights into the energy partition of thermal, nonthermal, CMEmechanical, and nonpotential magnetic energies (Emslie et al 2004(Emslie et al , 2005Saint-Hilaire & Benz 2005), the soft-hard-soft evolution of hard X-ray spectra compared with acceleration models (Grigis & Benz 2004, the low-energy cutoff of the electron spectrum (Sui et al 2005), the physics of the Neupert effect, i.e., the correlation between the thermal soft X-ray and the integral of the hard X-ray time profiles (Veronig et al 2005b), and the size dependence of solar flare spectral properties (Battaglia et al 2005). Other exciting RHESSI discoveries are the quasi-periodic hard X-ray pulsations that could be explained in terms of the MHD kink mode, which supposedly modulates the electron injection in a multiple flare-loop system .…”
Section: Rhessi Observationsmentioning
confidence: 99%